Documentary Survey Technique: A Study (Integral Research, 2025)
The documentary survey technique is an important research method that is used to collect and analyze information in various fields. This technique mainly carries out research work on the basis of available documents, records, reports, books, articles, and other written materials. Its purpose is to compile relevant data, perform statistical calculations, analyze it, and draw conclusions. The main advantages of the documentary survey technique include saving time and resources, selecting detailed and reliable data, access to documents, and comparative study of historical and current information. However, it also has some limitations, such as availability of documents, their authenticity, and dependence on the researcher's interpretation. The presented research technique is widely used in social sciences, historical research, policy analysis, and other academic fields. It allows researchers to conduct in-depth studies even without primary data collection.
Keywords: Documentary, survey, techniques, features, types, internal, external, study, analysis, suggestions etc.